2010
DOI: 10.1002/eji.200940102
|View full text |Cite
|
Sign up to set email alerts
|

How chronic viral infections impact on antigen‐specific T‐cell responses

Abstract: Persistent viral infections are, by definition, associated with ineffective antiviral immunity, in particular those infections caused by viruses that are highly productive and replicative (including HIV, HBV and HCV). The reasons for ineffective antiviral immunity in these types of infections are complex and manifold, and only recently a more comprehensive picture of the parameters responsible for attenuation of immune function is emerging. One reason for poor viral control in these types of infections is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(104 citation statements)
references
References 113 publications
(161 reference statements)
4
98
0
2
Order By: Relevance
“…In the search for an inducer of exhausted T cells, extensive studies have focused on PD-1 expression on HCV-specific CD8 ? T cells [98]. Urbani et al reported that the number of CD8 ?…”
Section: T Cell Responses In Chronic Hcv Infectionmentioning
confidence: 99%
“…In the search for an inducer of exhausted T cells, extensive studies have focused on PD-1 expression on HCV-specific CD8 ? T cells [98]. Urbani et al reported that the number of CD8 ?…”
Section: T Cell Responses In Chronic Hcv Infectionmentioning
confidence: 99%
“…Moreover, we analyzed the expression levels of PD-1, Tim-3, and LAG-3 ( Fig. 2A), all of which are known to negatively regulate T-cell effector function during certain chronic infections with highly replicative viruses [19]. We have not observed any differences in expression levels of Tim-3 and LAG-3 on M25-specific CD4 + T cells compared with those of endogenous CD4 + T cells, with the exception of PD-1 being upregulated on M25-specific CD4 + T cells compared with endogenous CD4 + T cells in the lungs and iLNs.…”
Section: Expansion Activation and Phenotype Of M25-specific Cd4 + Tmentioning
confidence: 99%
“…Functional exhaustion of T cells is observed in patients with chronic hepatitis or HIV infection and is associated with increased expression of inhibitory receptors, in- cluding PD-1 and Tim-3 (26). To gain insight into the mechanisms regulating the function of CMV-specific CD4 + T cells, the expression of PD-1 and Tim-3 was measured at the level of CMV and TT-specific CD4 + T during primary and chronic infection.…”
Section: Cd28 + Cmv-specific Cd4 + T Cells Express Increased Levels Omentioning
confidence: 99%